Differences in the public medical insurance systems for inflammatory bowel disease treatment in Asian countries - Shu Chen Wei (Intestinal Research, 2016)
Background/AimsThe cost of caring for patients with inflammatory bowel disease (IBD) is high. Without government support, the cost burden will unavoidably rest on the patients and their family. However, the government providing full support will place a large financial burden on the health-care systems of a country. The aim of this study is to understand the current status of public medical insurance systems in caring for IBD patients among Asian countries.MethodsQuestionnaires inquiring about the availability of public health systems; medical, diagnostic, and endoscopy costs; and coverage rate of biologics use were designed and sent to IBD experts in each of the Asian countries studied. The results were summarized according to the feedback from the responders.ResultsThe public health insurance coverage rate is high in Taiwan, Japan, South Korea, China, Hong Kong, and Singapore; but low in Malaysia and India. This probably affected the use of expensive medications mostly, such as biologics, as we found that the percentage of Crohn's disease (CD) treated with biologics were as high as 30%–40% in Japan, where the government covers all expenses for IBD patients. In India, the percentage maybe as low as 1% for CD patients, most of whom need to pay for the biologics themselves.ConclusionsThere were differences in the public health insurance systems among the Asian countries studied. This reportprovidesthe background information to understand the differences in the treatment of IBD patients among Asian countries.